Kurikulum Tahfidz Enterpreneurship tingkat Sekolah Menengah Pertama (SMP) - Abdulloh, Hotim (Tawazun: Jurnal Pendidikan Islam, 2022)
Tahfidz entrepreneurship curriculum at the junior high school level is needed to prepare a generation that is religious, has good morals, is independent and does not stand idly by for others. This study tries to find a model for implementing the tahfidz entrepreneurship curriculum at the junior high school level at Al-Amin Islamic Boarding School Tasikmalaya and SMPIT-TQ Ihya As-Sunnah Tasikmalaya. This study used descriptive qualitative method. The results of the study found that a good model for the tahfidz entrepreneurship curriculum at the junior high school level was as follows, first, tahfidz Alquran should ideally be carried out 10 hours per day. Second, entrepreneurship to foster the entrepreneurial spirit of students is carried out one day a week. Third, the condensation of official lessons can be carried out one day a week, and another important curriculum is the Islamic boarding school curriculum. Abstrak Kurikulum tahfidz entrepreneurship pada tingkat SMP sangat dibutuhkan untuk mempersiapkan generasi yang religius, berakhlak baik, mandiri dan tidak berpangku tangan pada orang lain. Penelitian ini mencoba menemukan model penerapan kurikulum tahfidz entrepreneurship pada tingkat SMP di Pondok Pesantren Al-Amin Tasikmalaya dan SMPIT-TQ Ihya As-Sunnah Tasikmalaya. Penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian menemukan bahwa model yang kurikulum tahfidz entrepreneurdship tingkat SMP yang baik adalah sebagai berikut, pertama, tahfidz Alquran idealnya dilaksanakan 10 jam per hari. Kedua, kewirausahaan untuk memupuk jiwa entrepreneurship siswa dilaksanakan satu hari per pekan. Ketiga, pemadatan pelajaran Dinas bisa dilaksanakan satu hari per pekan, dan kurikulum penting lainnya yaitu kurikulum kepesantrenan.